Changes in ownership forms and role of institutional investors in governing public companies in Malaysia: A research note. Issue 4 (2nd November 2015) - Annuar, Hairul Azlan
Abstract : Purpose: – The purpose of this paper is to ascertain whether different types of institutional investor in Malaysia are involved in the corporate governance of their investee companies, and, if yes, to what extent is the level of the involvement. Design/methodology/approach: – A qualitative approach, consisting of a series of interviews with 18 senior investment managers of different types of institutional investor, was chosen. Findings: – The findings suggest that lessons learnt from the fallout of the Asian crisis has made Malaysian institutional investors not only to be more prudent in managing their total funds and in making equities investment decisions, but has resulted in a more active participation in their "core" investee companies apart from merely discharging their voting rights. Interview analysis revealed that government-linked investment companies are championing the cause and could possibly affect the overall level of institutional investors' involvement, which bode well for the future of the corporate governance system of the country. Research limitations/implications: – Generalisations may be an issue when interviews are used as the method of inquiry. Also, the sample is not random, as access to many managers depended on recommendations. In addition, respondents were consciously selected to obtain different types of institutional investors that included government and non-government linked. Originality/value: – There is a lack of work on studying the involvement of institutional investors in developing countries, whereby previous work and literature review were predominantly based upon the experience of Western economies.